PERAN ASEAN DALAM MENANGANI KRISIS KEMANUSIAAN MYANMAR MELALUI KESEPAKATAN ASEAN FIVE POINT CONSENSUS - Ar Rasyid, Aviscenna Maulana; Rijal, Najamuddin Khairur (Indonesian Journal of International Relations, 2023)
This article aims to discuss the role of ASEAN in dealing with the humanitarian crisis after the 2021 coup in Myanmar through the ASEAN Five Point Consensus agreement. The discussion is carried out using the concept of ASEAN as an intergovernmental organization and a qualitative descriptive research method with primary and secondary sources from literature studies. The results of the study show that ASEAN has carried out its role as a regional organization, one of which has produced a consensus, namely the ASEAN Five Point Consensus in dealing with the situation in Myanmar. However, ASEAN experienced obstacles because the Myanmar military junta regime did not show good faith in respecting the points of agreement, making it difficult for ASEAN to play a role in resolving the humanitarian crisis in Myanmar. In conclusion, ASEAN has carried out its role as a regional organization as theorized, except for forcing its members to comply with set rules.